An Analysis of Breastfeeding-Related Education Needs for Postpartum Women at RSUP dr. Soeradji Tirtonegoro Klaten - Zulfa, Azizah Tiara; Nisman, Wenny Artanty; Parmawati, Ika; Saryati, Rumi (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Nurses have an important role in improving breastfeeding readiness through education. Thus, it is important to know the educational needs of postpartum women to help the breastfeeding process Nurses have an important role in improving breastfeeding readiness through education. Thus, it is important to know the educational needs of postpartum women to help the breastfeeding process. The objective of this study was to explore the educational needs postpartum women about breastfeeding.Method: This was a descriptive qualitative study. The research participants consisted of 10 postpartum mothers who gave birth at RSUP dr. Soeradji Tirtonegoro Klaten. The data were collected using in-depth interviews with semi-structured interviews and analyzed using thematic analysis.Result: The educational needs consisted of the needs for the expected educational materials, effective media and methods, and the implementation/technical aspects of education